ARIMA Model To Forecast The ISX60 Indicator: An Applied Study An Iraqi Financial Market - et. al., Azzam khalid Chyad, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to carry out the forecasting process in the Iraq Stock Exchange Index using the integrated regression model of moving averages "ARIMA", as the sample community is the Iraq Stock Exchange and the research sample is the 102 companies listed in the Iraq Stock Exchange and its number is (102) companies divided into seven sectors As follows (banks - communications - insurance - services - industry - hotels and tourism - agriculture, the study period was extended from (1/1/2019) to (1/31/2019), while statistical methods were used (arithmetic average - percentage change – T- test - the scatter plot – Q plot - and the autocorrelation coefficient), across applications (SPSS V25-Excle 2020- Py Charme2020) to compare results and test hypotheses, as it was found that the model was very good for predicting the full December sessions and was accurate at the reliability level (95%).